FAKTOR-FAKTOR PENYEBAB PERSALINAN EKSTRAKSI VAKUM DI CAMAR II RSUD ARIFIN AHMAD PEKANBARU - Siti Qomariah (Jurnal Kesehatan Husada Gemilang, 2022)
According to World Health Organization (WHO) in 2014 the Maternal Mortality Rate (AKI) in the world was 289,000 inhabitants. Maternal Mortality Rate in 2014 was 10 mothers of 21,692 live births while in 2013 was 9 mothers of 20,627 of live births. The purpose of this research was to see the factors of vacuum extraction labor. The type of this research wasdescriptive quantitative. The population in this researchwas the whole maternity who were in Camar II of Arifin Acmad Regional Public Hospital, Riau Province in 2015. The sampling technique of the research was saturated technique (138 people). The research was conducted on April 20, 2013 to May 6, 2015. The research instrument was table checklist. The data were analyzed by editing, coding, tabulating. The results showed, 104 respondents (75,36%) were 20-35 years old, the majority of first deliverywere 87 people (5.07%), the majority of hypertension were 17 people (12,31%), second stage of labor complications were 108 (78.26%). It can be concluded that the causes of vacuum extraction labor is on the second stage of labor complications (108 = 78,26%).